ANALISIS SWOT POLA GRAMEEN KOPERASI KONVENSIONAL & KOPERASI SYARIAH - Sakum; Andhika Alfathanah (Jurnal Ekonomi Syariah Pelita Bangsa, 2022)
This research is an empirical research conducted in 2014. This study aims to determine the working mechanism of Grameen in Amartha Micro Finance Cooperative and the working mechanism of sharia Grameen in Baytul Ikhtiar Cooperative. The analysis used is a SWOT analysis. Namely for mapping the strengths (strengths), weakness (weakness), opportunities (opportunity), and threats (threats).The research was conducted using a descriptive method, namely exploring and exploring problems regarding the working mechanism of Grameen and Grameen sharia in the Amartha Micro Finance Cooperative and the Baytul Ikhtiar Cooperative. The problems are explored through the data in the cooperative, as well as interviews with the customers of the cooperative. In addition, the data in the cooperative is data that have been documented in the cooperative. The results show that the Amartha Micro Finance Cooperative and the Baytul Ikhtiar Cooperative have different strengths, weaknesses, opportunities, and threats. So that different strategies are needed to increase the company's capacity and capability.